Data-informed Teacher Training in Islamic Schools to Impact Effective Professional Development - Nur kholis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article challenges the assumption that teacher training programs need not to be based on data-informed decisionmaking. It argues that such an approach neglects the contextual factors and the agency of the teachers in shapingtheir own professional development. Using a qualitative research method, the article presents a multiple case study ofthree islamic elementary schools in Pekalongan, Indonesia that have implemented data-informed teacher trainingprograms. The findings reveal that teacher forums play a crucial role in determining the content and format of thetraining programs, that islamic teachers face various challenges in adapting to the digital era, and that the foundationmanagement has a significant influence on the quality and sustainability of the training programs. The articleconcludes that teacher training programs should be more responsive to the needs and preferences of the teachers, ratherthan being imposed by mere trends and trial and error